Oxidative Alkenylation/Annulation of Benzimidates via Ruthenium(II)‐Catalyzed CH Activation to Generate 3‐Methyleneisoindolin‐1‐ones. Issue 2 (23rd December 2014) - Li, Xing Guang; Sun, Min; Liu, Kai; Liu, Pei Nian
Abstract: A novel ruthenium‐catalyzed oxidative alkenylation/annulation cascade reaction is described for synthesizing 3‐methyleneisoindolin‐1‐ones. In the protocol, the N H imidate is applied efficiently as a directing group in ruthenium‐catalyzed CH activation, generating various 3‐methyleneisoindolin‐1‐ones with high regio‐ and stereoselectivity in moderate to good yields. Abstract :